The Design Of Air Ex-Changer Device (Aed) To Generate Electricity From Waste Air Conditioning Exhaust (Wace) - Hussin, Rosniza; Ramachandran, Karthigeyen; Mohd Salleh, Zuliazura; Abd Rashid, Razlin (Progress in Engineering Application and Technology, 2020)
Abstract: The purpose of this study is to determine a medium for converting wind energy from air conditioning exhaust to kinetic energy and subsequently into electrical energy. This report majorly concerned about the design of air exchanger device (AED) to generate electricity from waste air conditioning exhaust for appropriate application and to evaluate the performance of AED. The idea is to use waste energy to generate electricity and to reduce the use of electricity. This significant research and design has been made in order to define additional clean energy sources in decreasing the primary electrical sources which is majorly using a fossil fuel as sources of energy. The carbon dioxide produces from the combustion process had led to greenhouse effect which is increasing the global temperature. The method that is used in this study is using wind energy to generate electricity by following the concept of wind turbine. The idea of developing this project is compared with 5 other similar methods which uses different renewable sources. The types of materials used in developing this project are voltage regulator, dynamo, voltage boost converter, mini fan, diode, capacitor, rechargeable battery and shaft. Upon determining the right materials and component, the design process needs to be conducted. The AED is designed in a way that allows the waste from the air conditioning air exhaust to rotate the mini fan that is connected to the dynamo. The electricity generated by dynamo will pass through the voltage boost converter to increase the voltage and will be stored to the rechargeable battery before used in appropriate applications. As a result of study, AED produces high voltage which can not only be stored in the rechargeable battery but also light up the LED. It is also capable to save the electricity of a single house which can then result to saving the global consumption.